Thrombocytosis in rheumatoid arthritis. Recurrent arterial thromboembolism and death. - Ehrenfeld, M (1977)
A patient with rheumatoid arthritis complicated by excessive thrombocytosis and recurrent thromboembolic events is presented. The platelet count correlated well with disease activity and thrombosis occurred when thrombocytosis was marked. The patient died from massive thrombosis of the aorta despite treatment with anticoagulants, corticosteroids, and azathioprine.